2010
DOI: 10.1074/jbc.m110.101485
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functionally Segregated Sarcoplasmic Reticulum Calcium Stores in Pulmonary Arterial Smooth Muscle

Abstract: In pulmonary arterial smooth muscle, Ca2+ release from the sarcoplasmic reticulum (SR) via ryanodine receptors (RyRs) may induce constriction and dilation in a manner that is not mutually exclusive. We show here that the targeting of different sarcoplasmic/endoplasmic reticulum Ca2+-ATPases (SERCA) and RyR subtypes to discrete SR regions explains this paradox. Western blots identified protein bands for SERCA2a and SERCA2b, whereas immunofluorescence labeling of isolated pulmonary arterial smooth muscle cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 53 publications
9
59
0
Order By: Relevance
“…It is possible that within the puncta, the RyR, STIM1, and CRAC channels localize in close proximity to each other but distant from SERCA. This hypothesis is supported by previous reports that RyR and SERCA may be segregated in different ER subcompartments (57,58). Spatial co-localization of RyR, STIM1, and CRAC channels would facilitate RyR activation by SOCE via the CICR mechanism and subsequent formation of discrete microdomains of low [Ca 2ϩ ] ER ("cold spots") in the vicinity of STIM1.…”
Section: Ryr Expression and Function Are Up-regulated Upon Primary Husupporting
confidence: 83%
“…It is possible that within the puncta, the RyR, STIM1, and CRAC channels localize in close proximity to each other but distant from SERCA. This hypothesis is supported by previous reports that RyR and SERCA may be segregated in different ER subcompartments (57,58). Spatial co-localization of RyR, STIM1, and CRAC channels would facilitate RyR activation by SOCE via the CICR mechanism and subsequent formation of discrete microdomains of low [Ca 2ϩ ] ER ("cold spots") in the vicinity of STIM1.…”
Section: Ryr Expression and Function Are Up-regulated Upon Primary Husupporting
confidence: 83%
“…Cells in mouse aorta and tail artery express the RYR1 transcript, though as expected, to a much lower extent than skeletal muscle ( Figure 2A) and the presence of the RYR1 Y522S mutation in the heterozygous state does not affect the expression of RYR1 ( Figure 2B) no of RYR2 and RYR3 (Supplementary Figure 3). RT-PCR on mRNA isolated from tail RyR1-mediated calcium release from subplasmalemmal stores causes activation of BK channels resulting in cellular hyperpolarization leading to vasodilation (35,36).…”
Section: Human Subjects Carrying Ryr1 Mutations Have a Mild Bleeding mentioning
confidence: 99%
“…The released calcium further activates release of calcium from the SR via RyR3 found at SR-lysosomes nanojunctions in a CICR manner (Kinnear et al, 2004(Kinnear et al, , 2008. After activation of RyR3, the RyR2 isoform is activated in a CICR manner, and the calcium released from the SR is propagated as a wave in the cytoplasm to activate contraction of SMCs (Kinnear et al, 2004(Kinnear et al, , 2008Clark et al, 2010). By use of a lysosome marker and labeled ryanodine, Kinnear et al (2008) demonstrated a close proximity between the lysosomes and ryanodine receptors.…”
Section: Examples Of Calcium Compartmentalization Involved In Vasculamentioning
confidence: 99%